Again, making Tanzania great: Magufuli's restorationist developmental nationalism. Issue 7 (2nd October 2020) - Paget, Dan
ABSTRACT: This article is about how ideologies legitimize authoritarianism. The literature argues that liberation nationalists discursively construct "liberation" as an ongoing struggle and justify their authoritarian rule until its completion. By recurrently postponing liberation, they extend this justification of authoritarianism. Nonetheless, their claim that the nation is part-way through liberation becomes less plausible over time. Liberation nationalism shares a discursive structure with a parallel class of developmental nationalisms. I analyse the ideology of President Magufuli and CCM in Tanzania. Instead of claiming that the nation is mid-transformation, they constructed the status quo as a corrupt deviation from a past order: "Nyerere's Tanzania". They conceived of this past order as a nation dedicated to industrial development which would lead to a transformed future. They advocated rupture with the present, the restoration of the past and the resumption of this transformative journey. Restorationism relieves liberation and developmental nationalisms of the rising rhetorical challenge of claiming that the nation has been on a transformative path since liberation. Therefore, Magufuli and CCM developed a variant upon liberation and developmental nationalisms, which also justifies authoritarianism. Unlike them, it remains rhetorically viable as the moment of liberation or development becomes distant. I call it restorationist developmental nationalism.